2022
DOI: 10.3390/ijerph19158888
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in the Prevalence of Diabetes in Argentina: A Repeated Cross-Sectional Study in Urban Women and Men

Abstract: This study measured the socioeconomic inequalities in the prevalence of diabetes between 2005 and 2018 in an urban Argentinian population. Data were obtained from the repeated cross-sectional surveys “National Survey of Risk Factors” (ENFR is its acronym in Spanish). From 2005 to 2018, four rounds of ENFR were administered to men and women over 18 years of age. Concentration curves (CC) and the Erreygers concentration index (ECI) were used to describe the socioeconomic inequalities in diabetes’ prevalence. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…A negative CI indicates disproportionate concentration of the outcome among the poorest, while a positive CI suggests inequality concentrated among the richest. The closer the absolute value of the CI is to one, the higher the level of inequality ( 19 ). The final analysis was performed using decomposition analysis to identify the contribution of each socioeconomic variable to the inequality of timing of ANC visits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A negative CI indicates disproportionate concentration of the outcome among the poorest, while a positive CI suggests inequality concentrated among the richest. The closer the absolute value of the CI is to one, the higher the level of inequality ( 19 ). The final analysis was performed using decomposition analysis to identify the contribution of each socioeconomic variable to the inequality of timing of ANC visits.…”
Section: Methodsmentioning
confidence: 99%
“…If the concentration curve is above this diagonal line, it means the outcome variable is more concentrated among poorer individuals. Conversely, if it lies below the diagonal line, it indicates a concentration among wealthier individuals (18). However, a concentration curve is not enough to measure the magnitude of inequality.…”
Section: Data Management and Analysismentioning
confidence: 99%
“…Women were usually more affected by their SES and the higher it was the lower was their risk of developing diabetes compared to men. [49][50][51] Addo et al, did a study on Ghanian adults residing in Europe based on data derived from the multicenter Research on Obesity and Diabetes among African Migrants (RODAM). They found that diabetes prevalence decreased with increasing educational level in Ghanaian men and women in Europe and in men in urban Ghana; however, it increased with increasing level of education in men and women in rural Ghana.…”
Section: Diabetes Prevalence and Its Association With Ses In 2003 And...mentioning
confidence: 99%
“…Mutyambizi et al, indicate that self-reported diabetes in South Africa is more common among rich people while undiagnosed diabetes is usually found among the poor. [11] Whereas some studies associate between higher diabetes prevalence and lower SES especially in women, [22,48,49] others link between higher diabetes prevalence and rich men with high SES. [58,59] Additionally, men with lower SES in South Africa usually work in jobs that necessitate physical activity.…”
Section: Vulnerable Groups Who Are At Risk Of Developing Diabetes In ...mentioning
confidence: 99%